2021
DOI: 10.3390/cells10020415
|View full text |Cite
|
Sign up to set email alerts
|

Adult Upper Cortical Layer Specific Transcription Factor CUX2 Is Expressed in Transient Subplate and Marginal Zone Neurons of the Developing Human Brain

Abstract: Cut-Like Homeobox 2 (Cux2) is a transcription factor involved in dendrite and spine development, and synapse formation of projection neurons placed in mouse upper neocortical layers. Therefore, Cux2 is often used as an upper layer marker in the mouse brain. However, expression of its orthologue CUX2 remains unexplored in the human fetal neocortex. Here, we show that CUX2 protein is expressed in transient compartments of developing neocortical anlage during the main fetal phases of neocortical laminar developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Embryonic birth-dating lineage tracing in monkeys and carnivores suggested that interstitial neurons shared the same developmental origin with subplate neurons and deep-layer cortical neurons [ 11 , 14 , 15 ]. The expression of cortical layer markers CUX2, TLE4, and FOXP1 were identified in the embryonic human subplate [ 30 ], these neurons were considered as immature migratory neurons that co-expressed with DCX [ 31 ]. However, whether interstitial neurons in the adult human brain expressed cortical neuronal markers remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic birth-dating lineage tracing in monkeys and carnivores suggested that interstitial neurons shared the same developmental origin with subplate neurons and deep-layer cortical neurons [ 11 , 14 , 15 ]. The expression of cortical layer markers CUX2, TLE4, and FOXP1 were identified in the embryonic human subplate [ 30 ], these neurons were considered as immature migratory neurons that co-expressed with DCX [ 31 ]. However, whether interstitial neurons in the adult human brain expressed cortical neuronal markers remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine+EPA rats upregulated brain Superoxide Dismutase 3 ( Sod3 ) gene, involved in anti-inflammation and neuroprotection in stress 148 . In addition, both fluoxetine and its combination with EPA reduced the expression of Cut Like Homeobox 2 ( Cux2; vs. stress) that regulates the development of dendrites, dendritic spines and synapses of neocortical neurons in mice, and has been linked to clinical affective disorders and schizophrenia 149,150 .…”
Section: Discussionmentioning
confidence: 99%
“…As both drugs treat clinical depression, and their combination is more efficient than monotherapy 152,153 , rats treated with fluoxetine+EPA show upregulated brain Superoxide Dismutase 3 ( Sod3 ) gene involved in anti-inflammation and neuroprotection in stress 154 . Both fluoxetine and fluoxetine+EPA reduced hippocampal expression of Cut Like Homeobox 2 ( Cux2) that regulates the development of dendrites, dendritic spines and synapses of neocortical neurons in mice, and has been linked to clinical affective disorders and schizophrenia 155,156 . Unlike EPA, LPS initiates an inflammatory response via both immune and non-immune factors 123 .…”
Section: Discussionmentioning
confidence: 99%
“…In the fetal cortex, during mid-gestation, the subplate becomes elaborated with three sublayers and more than twice as thick as the cortical plate above it (Kostović et al, 2019 ). Molecular (Miškić et al, 2021 ; Smith et al, 2021 ; Žunić Išasegi et al, 2022 ; Junaković et al, 2023 ; Kopić et al, 2023 ) and in utero functional MRI studies described temporal changes of cellular components and morphological dynamics of the three-layered subplate (Vasung et al, 2021 ; Taymourtash et al, 2023 ; Wilson et al, 2023 ). Another focus in the research field is implication of the subplate in disease conditions.…”
mentioning
confidence: 99%